AJHSSR 2022
DOI: 10.56805/ajhssr.2022.5.5.106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Profitability and Dividend Policy Towards Company Value of Indonesian Commercial Banks Registered in 2014-2019 Indonesia Stock Exchange

Abstract: This research aims to find out the description of company value also the impact of profitability and dividend policy towards company value of Indonesian Commercial Banks which are registered in Indonesia in 2014 through 2019. The profitability is measured by using Return on Asset (ROA), Return on Equity (ROE), dividend policy is measured by using Dividend Payout Ratio (DPR), and company value is measured by using the Price to Book Value (PBV). This research used secondary data collected from Indonesian Commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
4
4
0
1
Order By: Relevance
“…This means that firms with larger size tend to have higher stock return than those with smaller sizes. This finding is consistent with the findings from previous literature conducted in emerging countries such as Indonesia and Pakistan (Maratani, 2009;Intariani and Suryantini, 2020).…”
Section: Cupicsupporting
confidence: 93%
See 4 more Smart Citations
“…This means that firms with larger size tend to have higher stock return than those with smaller sizes. This finding is consistent with the findings from previous literature conducted in emerging countries such as Indonesia and Pakistan (Maratani, 2009;Intariani and Suryantini, 2020).…”
Section: Cupicsupporting
confidence: 93%
“…The regression results showed that firm size is significantly related to the stock return. This result is consistent with the previous literature (Fama andFrench, 1992, Johnson andSoenen, 2003;Maratani, 2009;Intariani and Suryantini, 2020). The results also showed a positive relation between the firm size and the stock return.…”
Section: Cupicsupporting
confidence: 93%
See 3 more Smart Citations